Creating an Unresourced Project with Oracle Primavera P6 PPM - Harris, Paul (Packt Publishing, 2021)
This course covers Primavera P6 Version 8 to Version 20 and explains the differences between the versions About This Video Workshop on navigating around the windows, creating your project, and maintaining the calendars Workshop on creating the Work Breakdown Structure, adding activities, and formatting the bar chart Workshop on adding relationships, scheduling calculations and activity network view, and constraints In Detail Primavera is an enterprise project portfolio management software. It includes project management, scheduling, risk analysis, opportunity management, resource management, and collaboration and control capabilities, and integrates with other enterprise software such as Oracle and SAP's ERP systems. This course aims to teach students the user interface and how to plan projects without resources on Oracle Primavera Project Manager P6 PPM Professional tool. You will start with getting introduced to Oracle Primavera Project Manager P6 PPM Professional. Then, you will understand how to create a new project and plan it simultaneously in the Primavera tool. You will also define calendars and create a Primavera Project WBS (Work Breakdown Structure). You will then learn about adding activities and organizing under the Work Breakdown Structure. Post that, you will be formatting the display and adding relationships. Finally, you will look at the activity network view and constraints in detail. By the end of the course, you will successfully learn planning without resources using the Primavera Project Manager P6 PPM Professional tool.
Online resource; Title from title screen (viewed July 28, 2021)
Keywords: Streaming video; Internet videos; Vidéo en continu; Vidéos sur Internet; streaming video; Electronic videos